Nickel-Catalyzed Cross-Coupling of Ammonia or Primary Alkylamines with (Hetero)aryl Sulfamates, Carbamates, or Pivalates - MacQueen, Preston M.; Stradiotto, Mark (Synlett, 2017)
A catalyst system capable of effecting the cross-coupling of ammonia or primary alkylamines with (hetero)aryl sulfamates, carbamates, or pivalates is reported for the first time. The air-stable nickel(II) pre-catalyst C1 tolerates a broad spectrum of heterocyclic functionality within both reaction partners, as well as ether, nitrile, pyrrole, trifluoromethyl, and boronate ester substituents. In the case of reactions involving primary alkylamines and (hetero)aryl sulfamates and carbamates, room-temperature cross-couplings were achieved.
Keywords: nickel; sulfamates; carbamates; pivalates; C–N cross-coupling; ammonia; primary alkylamines